Book Reviews. Issue 3 (1st December 2019) - Andrews, Naomi J.; Jackson, Simon; Wardhaugh, Jessica; Fogg, Shannon; Pearson, Jessica Lynne; Campbell, Elizabeth; Frader, Laura Levine; Cole, Joshua; Foster, Elizabeth A.; White, Owen
Abstract : Silyane Larcher, L'Autre Citoyen: L'idéal républicain et les Antilles après l'esclavage (Paris: Armand Colin, 2014). Elizabeth Heath, Wine, Sugar, and the Making of Modern France: Global Economic Crisis and the Racialization of French Citizenship, 1870–1910 (Cambridge: Cambridge University Press, 2014). Rebecca Scales, Radio and the Politics of Sound in Interwar France, 1921–1939 (Cambridge: Cambridge University Press, 2016). Claire Zalc, Dénaturalisés: Les retraits de nationalité sous Vichy (Paris: Éditions du Seuil, 2016). Bertram M. Gordon, War Tourism: Second World War France from Defeat and Occupation to the Creation of Heritage (Ithaca: Cornell University Press, 2018). Shannon L. Fogg, Stealing Home: Looting, Restitution, and Reconstructing Jewish Lives in France, 1942–1947 (Oxford: Oxford University Press, 2017). Sarah Fishman, From Vichy to the Sexual Revolution: Gender and Family Life in Postwar France (New York: Oxford University Press, 2017). Frederick Cooper, Citizenship between Empire and Nation: Remaking France and French Africa, 1945–1960 (Princeton: Princeton University Press, 2014). Jessica Lynne Pearson, The Colonial Politics of Global Health: France and the United Nations in Postwar Africa (Cambridge, MA: Harvard University Press, 2018). Darcie Fontaine, Decolonizing Christianity: Religion and the End of Empire in France and Algeria (New York: Cambridge University Press, 2016).